AKT1 has dual actions on the glucocorticoid receptor by cooperating with 14-3-3. (5th January 2017) - Habib, Tanwir; Sadoun, Ameera; Nader, Nancy; Suzuki, Shigeru; Liu, Wei; Jithesh, Puthen V.; Kino, Tomoshige
Abstract: Glucocorticoids are important therapeutic compounds for acute lymphoblastic leukemia (ALL). AKT1 or the protein kinase B is frequently activated in ALL, and contributes to the development of glucocorticoid resistance. We examined impact of AKT1 on glucocorticoid receptor (GR)-induced transcriptional activity in cooperation with phospho-serine/threonine-binding protein 14-3-3. AKT1 has two distinct actions on GR transcriptional activity, one through segregation of GR in the cytoplasm by phosphorylating GR at Ser-134 and subsequent association of 14-3-3, and the other through direct modulation of GR transcriptional activity in the nucleus. For the latter, AKT1 and 14-3-3 are attracted to DNA-bound GR, accompanied by AKT1-dependent p300 phosphorylation, H3S10 phosphorylation and H3K14 acetylation at the DNA site. These two actions of AKT1 regulate distinct sets of glucocorticoid-responsive genes. Our results suggest that specific inhibition of the AKT1/14-3-3 activity on the cytoplasmic retention of GR may be a promising target for treating glucocorticoid resistance observed in ALL. Highlights: AKT has 2 distinct actions on GR transcriptional activity in corporation with 14-3-3. One is segregation of GR in the cytoplasm through phosphorylation binding of GR to 14-3-3. The other is direct activation of GR transcriptional activity in the nucleus cooperating with 14-3-3. Specific modulation of these 2 actions of AKT1/14-3-3 is beneficial for ALL treatment.